Timescapes of Community Resilience and Vulnerability in the Circumpolar North - Robards, M.; Alessa, L. (ARCTIC, 2004)
Historical relationships between people and a changing Arctic environment (which constitute a social-ecological system, or SES) can offer insights for management that promote both social and ecological resilience. The continued existence of healthy renewable resources around communities is particularly important, as subsistence and commercial use of local resources are often the only practical avenues to healthy, long-term security for those communities. Our research draws on the position that SESs exist in an environment that is explicitly temporal: frequently cyclic, changing, contextual, and contingent. Therefore, the causes and effect of disturbances to SESs are rarely temporally linear; instead, they are characterized by a complex array of hysteretic effects and alternate (possibly repeating) states. The term 'timescapes' describes the time-space context element and its fundamental importance to sustainable practices. We investigate social-ecological timescapes of the circumpolar North in relation to four primary provisioning practices (hunting/gathering, pastoralism, agriculture, and market-based economy). Broadly, we identify distinct social-ecological states, interspersed with periods of change. For specific communities that have maintained their existence through a series of periods of profound change, we propose that elements of social and ecological resilience have been neither incrementally lost nor gained through time; rather, they have waxed and waned in accordance with specific, and sometimes repeating, conditions. To maintain their existence, we believe, communities have had to maintain their ability to recognize gradual or rapid changes in social, ecological, or economic conditions and reorganize themselves to adapt to those changes, rather than to any specific outcomes of a change. That is, they have adapted to a dynamic environment, not a preferred state. However, centralized Western management, despite fundamental flaws in accounting for local linkages between culture, economics, and the ...